Identités et territoires - Souheila HEDID (Lengas)
This is a return to a very large sociolinguistic survey that focused on socio-spatial mobility in the Algerian city. The focus is on the African diaspora and the presence of sub-Saharan migrant speakers in the city of Constantine. We are trying to understand the multiple configurations of their integration into this new welcoming society. In studies on mobility, the identity aspect inexorably occupies the largest part of this whole process and constitutes a real challenge for scientists.